NICE neonatal early onset sepsis guidance: greater consistency, but more investigations, and greater length of stay. Issue 3 (25th July 2014) - Mukherjee, Arindam; Davidson, Louise; Anguvaa, Lazarus; Duffy, Donovan Alistair; Kennea, Nigel
Abstract : Background: In August 2012, new national guidance (National Institute of Health and Care Excellence (NICE) CG149) for management of early onset sepsis (EOS) was introduced in the UK. The guidance outlined a consistent approach for septic screens in newborn infants based on risk factors, and suggested biochemical and clinical parameters to guide management. In particular, it advised a second C-reactive protein level (CRP) 18–24 h into treatment to help determine length of antibiotic course, need for lumbar puncture (LP), and suggested review of blood culture at 36 h. Objective: We evaluated impact of this guidance in our neonatal unit. Methods: We compared two time periods, before and following the guidance. We evaluated length of stay, second CRP 18–24 h into treatment, percentage of babies having LP and duration of antibiotics. Results: Before NICE guidance, 38.1% of screened babies stayed <72 h. This reduced to 18.4% following guidance. Before guidance, 20.9% babies stayed >5 days, which increased to 27.7% following NICE recommendations. Repeat CRP measurements increased from 45% to 97%. In 58% of these babies, repeat CRPs influenced management and hospital stay. An increase in LPs performed from 14% to 23% was noted. There were no positive blood cultures or LP results. Conclusions: We envisaged shorter hospital stays with new NICE standards, particularly, with the aim of 36 h blood culture reporting. However, repeat CRP led to further investigations, increased LPs and longer durations of treatment and stay. This, in turn, impacted on workload and cost, and influenced parental experience in the first few days of life.